Identification of Hub Genes and Therapeutic Targets in Lung Cancer Using Software Tools - Anbuselvi, S.; Saranya, S. (Asian Journal of Biological and Life Sciences, 2025)
Background: Lung cancer remains a leading cause of cancer deaths. Objective: Identify hub genes associated with lung cancer via GEO curation and PPI/network analyses to prioritize therapeutic targets. Methods: Functional enrichment (DAVID, ShinyGO), druggability assessment (ChEMBL, Pharos). Results: Top hub genes and enriched pathways reported; chemokine receptor activity and T-cell receptor related functions highlighted. Conclusion: Prioritized hub genes provide resources for experimental validation.
Keywords: Lung Cancer; Hub genes; PPI; Therapeutic targets